CHARACTERIZATION OF THE PSYCHOLOGICAL TYPOLOGY IN ESOPHAGEAL CANCER PATIENTS - Pinto, Stela Duarte; Rodriguez, Lorgio Henrique Diaz; Takeda, Flavio Roberto; Tacconi, Marcos Roberto; Sallum, Rubens Antonio Aissar; Cecconello, Ivan; Ribeiro Junior, Ulysses (Colegio Brasileiro Cirurgia Digestiva-cbcd, 2022)
Background: Esophageal cancer is an environment-related disease, and the most important risk factors are alcohol intake and smoking, in addition to gastroesophageal reflux in obese patients. The characterization of the patients' personality can contribute to the perception of how everyone adapts to the social environment and what relationship one can establish with themselves and with others.Aim: The aim of this study was to identify the psychological typology in patients with esophageal cancer.Methods: The psychological typology of patients was defined using the Typological Assessment Questionnaire. In addition, the aspects of psychological assessment were studied to access the particularities of each patient, especially their reaction to the diagnosis and the meaning attributed to the disease.Results: A total of 90 patients with esophageal cancer, aged over 18 years, who completed high school, and were interviewed at the first medical appointment, were included. The introverted attitude was predominant (83.33%). The most common psychological type was introverted sensation, with feeling as a secondary function (43.3%), and the second most frequent was introverted feeling, with sensation as a secondary function (24.4%). From this psychological assessment, a variety of defensive mechanisms were found to minimize distress. Most patients made use of adaptive defenses in the face of the illness process.Conclusion: The identification of the psychological typology allows the most effective assistance in directing the peculiar needs of each patient. In addition, it contributes to the care team to individualize treatments based on specific psychological characteristics.
Keywords: Personality; Esophageal Neoplasms; Psychological Tests; Psychological Theory; Surgical Oncology